Fabrication and Enhanced Electrocatalytic Activity of Three-Dimensional Sphere-Stacking PbO2 Coatings Based on TiO2 Nanotube Arrays Substrate for the Electrochemical Oxidation of Organic Pollutants. Issue 13 (9th November 2017) - Wang, Zhicheng; Mao, YuLu; Xu, Mai; Wei, Yijun; Hu, Yunhu; Zhu, ChuanGao; Fang, Wenyan; Wang, Fengwu
Abstract : The three-dimensional sphere-stacking PbO2 coatings based on one-dimensional TiO2 -NTs/Ti substrate (3D-sphere PbO2 ) were prepared without other three-dimensional templates, only by using a simple pulse electrodeposition method. The surface morphology, compositions and crystallographic structure of 3D-sphere PbO2 electrode were investigated fully by using the field emission scanning electron (SEM), X-ray diffractometer (XRD) and energy dispersive X-ray spectroscopy (EDX), respectively. The comparative studies between 3D-sphere PbO2 electrode and traditional flat PbO2 electrode (flat-PbO2 ) indicated that the 3D-sphere PbO2 electrode with novel structure had smaller grain size. The electrochemical performances of the 3D-sphere PbO2 electrode were carried out by using cyclic voltammograms (CV), linear sweep voltammograms (LSV), electrochemical impedance spectroscopy (EIS) and accelerated service life, respectively. The results show that the 3D-sphere PbO2 electrode has larger electrochemical active surface area, higher oxygen evolution potential and lower charge transfer resistance, leading to it possesses better stable service life on process of degradation than that the flat-PbO2 electrode. Furthermore, the 3D-sphere PbO2 electrode showed the best performance on degradation of phenol in simulated wastewater by bulk electrolysis. The removal efficiency of phenol could reach about 96.5% after 120 min under the optimal current density (30 mA cm −2 ) at room temperature, which was higher than that by using the flat-PbO2 electrode (73.1%). In addition, the reaction rate constant ( k ) of 3D-sphere PbO2 electrode degrading phenol solution was 0.0277 min −1 which was 2.56 times larger than that of flat-PbO2 electrode (0.0108 min −1 ). Summarily, the 3D-sphere electrode is a promising electrode in treating wastewater.